(untitled) (JURNAL KEPERAWATAN, 2015)
Abstract: The postpartum period is often a very worrying time for a woman who first became a mother because it is required to be able to breastfeed and care for her baby. A mother’s decision to breastfeed or not related to the previous experience of breastfeeding in children. First-time mothers breastfeed considered inexperienced compared with mothers who already had previous breastfeeding experience. The demands of breastfeeding for the mother will feel heavy so that it can lead to psychological disorders such as anxiety. The aim of research to determine differences in the level of anxiety in the process of breastfeeding between primiparous and multiparous mothers in Pancaran Kasih GMIM Hospital of Manado. Design of this reseacrh is descriptive analytic with cross sectional study approach, a population that is all breastfeeding mothers who met the inclusion criteria. The research sample is 52 respondents obtained by using purposive sampling technique. The instruments used are questionnaire data themselves and scale levels of anxiety. The results of the statistical test using the Mann-Whitney test at 95% significance level (Ã¡ 0.05%), then the obtained value Ã± = 0.001. This means that the value of Ã± Ã¡ (0.05). Thus that there are different levels of maternal anxiety in the process of breastfeeding between primiparous and multiparous mothers in Pancaran Kasih GMIM Hospital of Manado. Suggestions for nursing mothers so much more to find out information about psikoligis changes that occur after childbirth, especially when breastfeeding and ways to minimize anxiety. Keywords: Anxiety Level In Process Breastfeeding, Primiparous, Multiparous. Abstrak: Masa pasca persalinan sering merupakan waktu yang sangat mencemaskan bagi seorang wanita yang baru pertama kali menjadi ibu karena dituntut untuk dapat menyusui dan merawat bayinya. Keputusan ibu untuk menyusui atau tidak berkaitan dengan pengalaman menyusui pada anak sebelumnya. Ibu yang pertama kali menyusui dianggap belum berpengalaman dibandingkan dengan ibu yang sudah memiliki pengalaman menyusui sebelumnya. Tuntutan menyusui bagi seorang ibu akan dirasa berat sehingga dapat menimbulkan gangguan psikologis seperti kecemasan. Tujuan penelitian untuk mengetahui perbedaan tingkat kecemasan dalam proses menyusui antara ibu primipara dan multipara di RS Pancaran Kasih GMIM Manado. Desain penelitian yaitu deskriptif analitik dengan rancangan cross sectional, populasi yaitu semua ibu menyusui yang memenuhi kriteria inklusi. Sampel penelitian ini 52 responden yang didapat dengan menggunakan teknik purposive sampling. Instrumen yang digunakan yaitu kuesioner data diri dan skala tingkat kecemasan. Hasil uji statistik menggunakan uji Mann-Whitney pada tingkat kemaknaan 95% (Ã¡ 0,05%), maka didapatkan nilai Ã± = 0,001. Ini berarti bahwa nilai Ã± Ã¡ (0,05). Dengan demikian bahwa terdapat perbedaan tingkat kecemasan ibu dalam proses menyusui antara ibu primipara dan multipara di RS Pancaran Kasih GMIM Manado. Saran untuk ibu menyusui agar lebih banyak mencari informasi mengenai perubahan psikoligis yang terjadi pasca persalinan terutama saat menyusui dan cara untuk meminimalisir kecemasan. Kata kunci: Tingkat Kecemasan Dalam Proses Menyusui, Primipara, Multipara.